INCLUSIVE EDUCATION PRACTICES IN INDONESIAN ELEMENTARY SCHOOLS: PLANNING, IMPLEMENTATION, AND EVALUATION - matius kurniawan; ngurah ayu nyoman murniati; muhamad Prayito (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the implementation of inclusive education at SDN Susukan 04, East Ungaran District, using a qualitative case study design. Data were collected through in-depth interviews, classroom observations, and document analysis, and validated through methodological and source triangulation. The findings show that planning was conducted through goal formulation, needs identification, and the development of adaptive programs integrated into the RKS/RKAS. Implementation involved curriculum modification, service accommodation, and the deployment of special education teachers to support 29 students with special needs across 13 classes. Evaluation was carried out systematically to measure goal attainment and identify barriers. The school demonstrated progress in fostering social acceptance, self-confidence, and empathy among students, consistent with the principles of inclusion and Social Role Valorization (SRV). However, challenges persist in teacher competency, parental involvement, and the adequacy of adaptive learning media. Strengthening professional development and building a comprehensive support system are essential for advancing transformative inclusion.